2016
DOI: 10.18632/oncotarget.11121
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-associated fibroblasts affect sensitivity to oxaliplatin and 5FU in colorectal cancer cells

Abstract: The importance of tumor microenvironment (TME) as a relevant contributor to cancer progression and its role in the development of de novo resistance to targeted therapies has become increasingly apparent. However, the mechanisms of microenvironment-mediated drug resistance for nonspecific conventional chemotherapeutic agents, such as platinum compounds or antimetabolites, are still unclear.Here we describe a mechanism induced by soluble factors released by carcinoma-associated fibroblasts (CAFs) that induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 49 publications
(49 reference statements)
1
31
0
Order By: Relevance
“…Higher levels of phosphorylated CHK2 consistent with lower CDC25B expression have been observed in 5‐FU‐treated cells cultured in CAF‐CM 56 . Moreover, CAF soluble factors stimulate and activate PI3K/AKT/mTOR and JAK/STAT pathways as well as the subsequent nuclear translocations of p38, AKT, and STAT activated forms, which increase Survivin expression 56 . Therefore, STAT3 constitutes a promising target to overcome CAF‐mediated CRC 5‐FU resistance, as STAT3 inhibition sensitizes CRC cells to 5‐FU even in the presence of CAF‐CM.…”
Section: Tumor Microenvironmentsupporting
confidence: 53%
See 1 more Smart Citation
“…Higher levels of phosphorylated CHK2 consistent with lower CDC25B expression have been observed in 5‐FU‐treated cells cultured in CAF‐CM 56 . Moreover, CAF soluble factors stimulate and activate PI3K/AKT/mTOR and JAK/STAT pathways as well as the subsequent nuclear translocations of p38, AKT, and STAT activated forms, which increase Survivin expression 56 . Therefore, STAT3 constitutes a promising target to overcome CAF‐mediated CRC 5‐FU resistance, as STAT3 inhibition sensitizes CRC cells to 5‐FU even in the presence of CAF‐CM.…”
Section: Tumor Microenvironmentsupporting
confidence: 53%
“…This cell cycle arrest seems to be mediated by the activation of G 2 /M checkpoint kinase 2 (CHK2) and the subsequent decrease in expression of cell division cycle 25B (CDC25B, a phosphatase that enables a cell to resume the cell cycle after its arrest induced by DNA damage). Higher levels of phosphorylated CHK2 consistent with lower CDC25B expression have been observed in 5‐FU‐treated cells cultured in CAF‐CM 56 . Moreover, CAF soluble factors stimulate and activate PI3K/AKT/mTOR and JAK/STAT pathways as well as the subsequent nuclear translocations of p38, AKT, and STAT activated forms, which increase Survivin expression 56 .…”
Section: Tumor Microenvironmentmentioning
confidence: 89%
“…They produce growth factors that activate p38 and STAT3 in CRC cells, and p38 inhibition can reverse drug resistance [129].…”
Section: P38 Enhancing Resistance To Targeted Therapies and Chemothermentioning
confidence: 99%
“…Recent studies have shown dysregulation of miRNAs in stromal cells in various cancers . High miRNA‐21 expression in CAFs was associated with a poor prognosis in lung adenocarcinoma, suggesting that at least some miRNAs are associated with cancer progression . In the present study, 10 of the 13 miRNAs evaluated were downregulated (hsa‐miRNA‐130a‐3p, hsa‐miRNA‐143‐3p, hsa‐miRNA‐206, hsa‐miRNA‐195‐5p, hsa‐miRNA‐27a‐3p, hsa‐miRNA‐19a‐3p, hsa‐miRNA‐34b‐3p, hsa‐miRNA‐186‐5p, hsa‐miRNA‐191‐5p and hsa‐let‐7a‐5p), and 3 miRNAs (hsa‐miRNA‐21‐5p, hsa‐miRNA‐31‐5p and hsa‐miRNA‐27b‐3p) were upregulated, in stromal cells from CRC compared with non‐cancer specimens.…”
Section: Discussionmentioning
confidence: 46%